Factors affecting intention to use M-wallet / Nurul Syafiqah Norazman - Norazman, Nurul Syafiqah (Faculty of Business and Management, 2020)
The purpose of this study is to examine the factors that affecting the intention to use mobile wallet (M-wallet), in this digital technology era of technology advance that can influence people to use M-wallet. In additional, it is also meant to analyse if the independents variables can influence the factors affecting intention to use M-wallet system. This is questionnaires has been answer by random people that stay at Petaling Jaya City. A questionnaire was completed reflecting their responses to five constructs which is their intention to use, perceived ease of use, perceived behavioural control, compatibility, and trust. Convenient sampling technique was used to distribute the questionnaires to random respondents. Subsequently, the data collected were transferred into the SPSS program and analysed. The data went through several statistical analyses such as Frequency Analysis, Reliability Analysis, Pearson Correlation Analysis, and Multiple Regression Analysis. The outcome was confirmed that independents variables are positively related to the factors affecting the intention to use M-wallet. Lastly, the findings of this research study can be beneficial to the entities involved in cashless society and future researchers.